Associations between genetic variants in folate and drug metabolizing pathways and relapse risk in pediatric acute lymphoid leukemia on CCG-1952. Issue 2 (2015) - Vujkovic, Marijana; Kershenbaum, Aaron; Wray, Lisa; McWilliams, Thomas; Cannon, Shannon; Devidas, Meenakshi; Stork, Linda; Aplenc, Richard
Abstract: Genetic variation in drug detoxification pathways may influence outcomes in pediatric acute lymphoblastic leukemia (ALL). We evaluated relapse risk and 24 variants in 17 genes in 714 patients in CCG-1961. Three TPMT and 1 MTR variant were associated with increased risks of relapse (rs4712327, OR 3.3, 95%CI 1.2–8.6; rs2842947, OR 2.7, 95%CI 1.1–6.8; rs2842935, OR 2.5, 95%CI 1.1–5.0; rs10925235, OR 4.9, 95%CI 1.1–25.1). One variant in SLC19A1 showed a protective effect (rs4819128, OR 0.5, 95%CI 0.3–0.9). Our study provides data that relapse risk in pediatric ALL is associated with germline variations in TPMT, MTR and SLC19A1. Highlights: Genetic variants in the folate pathway may influence ALL outcome. We evaluated 24 SNPs in 17 genes on relapse risk in pediatric ALL. Three TPMT variants were associated with an increased risk of relapse. One MTR variant was positively associated with risk of relapse. One variant in SLC19A1 showed a protective effect on relapse. TPMT, MTR and SLC19A1 are associated with relapse risk in pediatric ALL.